Temperantia, Golden Mean of Seneca the Younger, Roman Stoic - Budzanowska-Weglenda, Dominika (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
Seneca’s philosophical writings concern a virtue, among others also the virtues of justice, temperance (or moderation), fortitude and prudence. They are four virtues from the time of St. Ambrose called cardinal. Seneca gives this definition of the virtue temperantia: “cupiditates refrenare” – to confine one’s desires. So the temperance is practising self-control, abstention and moderation. Seneca discuses it very often in a wider context of the different virtues, with which it’s tightly connected according to a stoical idea of the inseparability of the virtues. He claims that we have to learn virtue. Seneca reminds that life is not easy and only the indications of the philosophy concerning virtue preserve from the unjust fortune.